Semiosi e colonialità in Palestina Riflessioni decoloniali sulla guerrilla visuale contro il muro israeliano (Altre Modernità, 2021)
The present essay looks at the Palestinian question within the field ofartistic activism (artivism), which, through a myriad of graffiti (amongwhich Banksy’s, Joy van Erven’s and Blu’s), offers a sort of counter-semiosis within thecoloniality of power (Quijano), in the attempt to symbolically knock down the Israeliwall. This wall-border becomes a herida abierta that bleeds, in the words of GloriaAnzaldúa, the global south’s blood, forced to clash against the global north’swalls, Israel being the product of the latter (Said, Question). This wall-border becomes“global” to the extent that the defence barrier, as it is called by the Israeli, or apartheidwall, as called by the Palestinians, has become a sort of global canvas on which atransnational visual guerrilla is fought. This fight is here interpreted through the lensof decolonial thought and, to put it with Walter Benjamin, from the perspective of thetradition of the oppressed.
Keywords: Palestine; walls; decolonial thinking; coloniality; visual semiosis